HUBUNGAN KORDINASI MATA DAN KAKI DAN POWER OTOT TUNGKAI TERHADAP HASIL SERVICE ATAS DALAM PERMAINAN SEPAKTAKRAW DI KLUB PCR PEKANBARU - Yusuf, Novri; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: The aim of this study is to determine whether there is a connection between eye and foot coordination and leg muscle power with the results of top service in the sepaktakraw game in the PCR Pekanbaru club. The sample of this study was the 6 players of the Sepaktakraw club PCR Pekanbaru. The sampling technique was taken in total (total sampling) or the technique of taking the entire sample on the Pekanbaru PCR club sepaktakraw players, for a total of 6 people. The results of the correlation on Pekanbaru PCR club sepaktakraw players where the first analysis between eye and foot coordination X1 and Y where rtab at a significant level ɑ (0.05) = r_calculate (0.925) <r_tab (0.878), meaning that the hypothesis is accepted and there is a moderate relationship between coordination eyes and feet to the results of the best service to the PCR sepaktakraw players Kluh Pekanbaru. From the calculation of the second analysis of X2 and Y, where r_tab is at a significant level ɑ (0.05) = r_calculated (0.990) <r_tab (0.878), this means that the hypothesis is accepted and there is a moderate relationship between leg muscle strength from the top controls of the Pekanbaru PCR club sepaktakraw players. The third analysis of the relationship of eye and foot coordination (X1) leg muscle strength (X2) with the results of service above (Y) where rtab can be at a significant level ɑ (0.05) = r_calculate (0.960) <r_tab (0.878) concluded that the relationship between (X1) and (X2) with (Y) or the relationship between eye and foot coordination and leg muscle power with the results of top service in a sepaktakraw game at the PCR Pekanbaru club in moderate intervention.Key Words: Eye and Foot Coordination, Leg Muscle, Upper Service